Republic of Serbia : Financial Sector Assessment Program Update; Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Financial Sector Assessment Program (FSAP) Update for Serbia. The assessment reveals that the financial system of Serbia has successfully weathered the global financial crisis, but faces the challenge of a possible further deterioration of the economic environment, with attendant effects on asset quality. The banking sector is highly capitalized and liquid, and displays considerable resilience in stress tests. Several important supervisory challenges remain despite an improvement in the supervisory framework since the 2005 FSAP.